(untitled) (TERRA LATINOAMERICANA, 2026)
Soils are the largest reservoir of carbon in terrestrial ecosystems. Meadows have been established to of fer a dif ferent source of forage and show high potential in carbon sequestration. This study aimed to evaluate the seasonal changes in the concentrations of soil organic carbon, total nitrogen, vegetative coverage, and the physicochemical properties of the soil in a mild climate meadow in Durango. The study was carried out in a mild climate meadow during the four seasons of the year, in which the vegetative coverage, dominant species, physicochemical properties, organic carbon, and nitrogen of the soil were determined. Vegetative coverage was dif ferent between seasons (p < 0.05); the percentage of herb decreased in winter, whereas the percentage of nude soil was lower in summer compared to the other seasons. On the other hand, the lowest values of organic matter and organic carbon in soil were found in fall (p < 0.05), therefore, the C:N ratio was also lower (p < 0.05). Carbon accumulated in soil increased from 21 Mg C ha-1 in fall to 27.5 ton C ha-1 in summer (p < 0.05); apparent density and total nitrogen showed no changes among seasons (p < 0.05). The results suggest that mild meadows have a high potential for carbon sequestration to reduce GHG emissions and contribute to climate change mitigation.